Mechanisms of traditional Chinese medicine regulating polycystic ovary syndrome through gut microbiota: a review - Jiang, Xiaomei; Wang, Yongfeng; Hua, Yu; Tang, Hong; Li, Heyue (Frontiers in Endocrinology, 2025)
Polycystic ovary syndrome (PCOS) is a prevalent endocrine disorder that adversely affects women’s reproductive and metabolic health conditions. Recent studies have highlighted the significant contributory role of gut microbiota in the pathogenesis of PCOS, indicating a complex interplay between the microbiome and the syndrome’s clinical manifestations. Given this connection, Traditional Chinese Medicine (TCM), a well-established therapeutic approach, has demonstrated potential efficacy in modulating gut microbiota and alleviating symptoms associated with PCOS. This review aims to summarize and analyze current research on the effects of TCM on gut microbiota in individuals with PCOS, exploring underlying mechanisms and relevant findings to provide insights for future clinical applications and improve understanding of TCM’s role in managing PCOS.